Integrated data mining environment in CRM solution. A case study of applied data mining techniques in CRM - IOUNNAS, Bilal; Supervised: Mokhtari, RABEH (University of M'sila, 2011)
Supporte& by technologies of Customer Satisfaction, Informarion Technology, and Dan mining, etc., CRM aims to enhance the and performance of the businesses by improving the customer satisfaetion and loyalty. CRM is now becoming a popular management methodology in manufacturing, sales, marketing, and finance. Based previous literaturo we illustrate how data mining can be very useful tools for CRM solution by shown data mining models in this kind of application.
Keywords: BI, CRM, Data mining, Sales, Marketing, Literature view.